Prevalence and factors associated with tobacco use among pregnant and breastfeeding mothers in India: insights from the National Family Health Survey-5 (2019–21) - Pradhan, Rachita; Dandsena, Rutuparna Sibani; Singh, Sneha; Ghosal, Shishirendu; Bhattacharya, Debdutta; Kanungo, Srikanta; Pati, Sanghamitra (Frontiers in Public Health, 2025)
BackgroundTobacco use remains a major public health concern, particularly in low- and middle-income countries, which account for 80% of the world’s tobacco users. In India, smokeless tobacco (SLT) use is higher among women, likely due to factors such as financial dependence resulting from limited occupational opportunities, peer influence, and gender inequality. Tobacco consumption in any form poses serious health risks to both mothers and their children.ObjectivesThis study aims to estimate the prevalence and factors associated with smoking tobacco and SLT among pregnant and breastfeeding mothers from the fifth National Family Health Survey (2019–21) (NFHS-5) in India.MethodsAfter excluding outliers, 722,933 women of reproductive age (24,368 pregnant, 102,080 breastfeeding, and 592,699 non-pregnant/non-breastfeeding mothers) were eligible for this cross-sectional secondary data analysis. Descriptive statistics are presented as means with standard deviations (continuous variables) or frequencies (categorical variables), with a 95% confidence interval as a measure of uncertainty. The magnitude of the influence on the covariates of tobacco consumption was estimated using univariate and multivariate logistic regressions.ResultsApproximately 3.2% of mothers reported using tobacco during their current pregnancy or while breastfeeding, with a strong preference for SLT, which was over 13 times more common than smoking tobacco. Significant predictors of SLT consumption included tribal ethnicity [AOR: 2.20 (1.95–2.48)] and early motherhood [AOR: 1.12 (1.08–1.16)]. Notably, mass media awareness campaigns were ineffective in preventing SLT use among mothers [AOR: 1.49 (1.43–1.57)]. A marked difference in prevalence was observed between pregnant (2.48%) and breastfeeding (3.34%) mothers, suggesting a potential postpartum relapse. These findings underscore the potential role that Accredited Social Health Activists (ASHAs) can play during antenatal care (ANC) visits by providing consistent support for tobacco cessation.ConclusionTobacco use poses serious health hazards not only to the mother but also to the developing child. Our findings indicate a lack of management and awareness, underscoring the urgent need for reforms in tobacco production and distribution to ensure improved maternal care and child health outcomes.